Metamorfosis Congklak - Dwi Agus Susilo (SULUH: Jurnal Seni Desain Budaya, 2018)
Congklak is one of the typical indonesia traditional games are made of stone, wood, plastik and one of the result of culture and art that deserves to be preserved. In ancient times congklak game done in the gazebo, patio homes or under a tree by holding the cushion. Young women and children will play spare time is after completion help parent’s work and finished learning. How to play performed by two people using cangklak board and grains are made of gravel / tamarind seeds and brown seed with a number of 70.84 and 98 grains depends on the number of large holes on each side, the rest of the small holes that are faces each other.This processwill berealized congklak metamorphosis into works of art that use waste wood powder coconut, of course this work is not independent of the other ingredients, namely resins, catalysts, iron columns 8 mm, nails, glue alteco and multiplex 2 mm. Being metamorphosis in question in a creative process of art processing base material by considering technique that puts the character and funcion of the basic shape change.